ALVEOLAR RHABDOMYSARCOMA SURGICAL TREATMENT WITH ISCHIUM AND PUBIC INVASION IN A MIX BREED CAT - Adi, Agil Putri; Pemayun, I Gusti Agung Gde Putra; Wirata, I Wayan (Buletin Veteriner Udayana, 2025)
Alveolar rhabdomysarcoma is a musculoskeletal malignant tumor of striated muscle origin rarely found in cats with bone invasion. Rhabdomysarcoma is classified based on pathological clinical features and genetic abnormalities identified into 4 subtypes namely embryonic, alveolar, spindle cell/sclerosis, and pleomorphic. This paper aims to diagnose and discuss the surgery to remove a tumor mass in a case of RMS in a cat on the caudal sinister limb. A mixed-breed cat named Moy, a non-sterilized, non-vaccinated female, 2 years old and weighing 2 kg, presented with complaints of a hard lump on the caudal sinister limb, difficulty defecating and urinating, and decreased appetite and drinking. The cat was kept free-ranging and fed ad libitum with boiled rice and fish. Histopathology showed the cat was diagnosed with alveolar rhabdomyosarcoma. The cat underwent surgical removal of the tumor mass. Postoperatively the cat was given cefotaxime antibiotic (PT. Dankos Farma Tbk., Jakarta, Indonesia) at a dose of 25 mg/kg BW intravenously. The cat did not progress well and died 7 hours postoperatively. The diagnosis must be promptly out to prevent the tumor mass enlarging and invading surrounding tissues. General anesthesia is required to avoid cumulative effects, which can be administered through inhalation or using propofol.